Correlation Between Serum Interleukinslevels with Anthropometric Data and Lipid Profiles in Obese Iraqi Women With Polycystic Ovary Syndrome - Jasim, Ruaa A.; Umran, Mahfoodha A.; Humadi, Esraa H. (Iraqi Journal of Science, 2020)
This study was performed to assess the correlation of serum interleukins (ILs) levels with anthropometric data and lipid profile status in blood samples obtained from 100 Iraqi obese women with polycystic ovary syndrome PCOS. Obese non PCOS healthy women (n=75) matching in age (19-38 years) and body mass index(29.9-33.4kg/m2) served as a control group. The samples were collected from Kamal Al-Samurai Teaching hospital during the period of December 2017- June 2018.ELISA kits were used to measure serum levels of IL-6,IL-10,IL-18, IL-29,IL-33,tumor necrotic factor (TNF-Î±),high sensitive C-reactive protein (hsCRP), insulin, total testosterone, and sex hormone binding globulin(SHBG).The biochemical measurements of blood glucose and lipid profile were performed by conventional colorimetricmethods. The results demonstrated significant differences(P < 0.01) in serum levels of all interleukins and lipid profile parameters in obese PCOS in comparison with obesenon PCOS control women.In addition, PCOS women had higher insulin and FAI levels in comparison to non PCOS women. The findings suggest that androgen excess, indicated by high free androgen index (FAI),might serve as an indicator of a prediabetic status, as it might promote insulin resistance and ð›½-cell dysfunction in PCOS women. Circulatory interleukin levels in obese PCOS women may act on the development of insulin resistance and androgen oversupply in PCOS,suggesting that high serum ILs levels were related to insulin resistance (IR) and androgen excess but not to body mass index. A high IL level is not an elemental characteristic of PCOS, but it may act in promoting IR and hyperandrogenism of PCOS.